A comparative review of short and long neuropeptide F signaling in invertebrates: Any similarities to vertebrate neuropeptide Y signaling? - Nässel, Dick R.; Wegener, Christian (Peptides (New York, N.Y. : 1980), 2011)
► This review summarizes information on neuropeptide F (NPF) and short NPF (sNPF) in invertebrates. ► They are distinct families of peptides with characteristic prepropeptide organization. ► NPFs and NPF receptors are ancestrally related to vertebrate neuropeptide Y and its receptors. ► Bona fide sNPFs appear to exist only in arthropods. ► NPFs regulate feeding, metabolism and reproduction, whereas NPFs have more pleiotropic functions. Neuropeptides referred to as neuropeptide F (NPF) and short neuropeptide F (sNPF) have been identified in numerous invertebrate species. Sequence information has expanded tremendously due to recent genome sequencing and EST projects. Analysis of sequences of the peptides and prepropeptides strongly suggest that NPFs and sNPFs are not closely related. However, the NPFs are likely to be ancestrally related to the vertebrate family of neuropeptide Y (NPY) peptides. Peptide diversification may have been accomplished by different mechanisms in NPFs and sNPFs; in the former by gene duplications followed by diversification and in the sNPFs by internal duplications resulting in paracopies of peptides. We discuss the distribution and functions of NPFs and their receptors in several model invertebrates. Signaling with sNPF, however, has been investigated mainly in insects, especially in Drosophila. Both in invertebrates and in mammals NPF/NPY play roles in feeding, metabolism, reproduction and stress responses. Several other NPF functions have been studied in Drosophila that may be shared with mammals. In Drosophila sNPFs are widely distributed in numerous neurons of the CNS and some gut endocrines and their functions may be truly pleiotropic. Peptide distribution and experiments suggest roles of sNPF in feeding and growth, stress responses, modulation of locomotion and olfactory inputs, hormone release, as well as learning and memory. Available data indicate that NPF and sNPF signaling systems are distinct and not likely to play redundant roles.